Unveiling the Space Economy from an Economical and Environmental Perspective with Special Reference to India - Choudhary, Pooja; Kumar, Neeraj; Ahmad, Alam; Akhtar, Samreen (International Journal of Economics and Financial Issues, 2025)
Space Economy includes any activity that involves exploring, researching, understanding, managing and utilizing space. The present article includes the development, significant actors, country-specific spending, environmental effects, and economic significance of the space economy with particular reference to India. The budgets of the major spacefaring countries and highlights of national spending on space programs are also discussed. It emphasizes that while developing and less developed nations find it difficult to afford space programs, those with high GDPs can often invest in space research. The connection between the space economy and the environment is also examined, along with the advantages of satellite-based Earth monitoring for the environment and studies on climate change, as well as the production of space trash and efforts to mitigate its effects. Finally, the economic contribution of the space economy is studied, highlighting its significance in raising global GDP through various enterprises and endeavors.